Pendampingan Nasabah BTPN Syariah melalui Program Bestee terhadap Perkembangan UMKM pada MMS Tembelang Jombang - Munawwaroh, Anita; Prasmala, Erfitra Rezqi; Jati, Putri Karlina (JPM PAMBUDI, 2024)
Bestee BTPN Syariah is a program that aims to provide training and skills development to the community, especially for women in rural areas. This program is designed to empower customers engaged in UMKM sector by providing knowledge and skills that can improve their economic welfare. The marketing system for UMKM products owned by BTPN Syariah customers in Tembelang District is still not optimal, so routine assistance is needed to increase the income of UMKM owned by BTPN Syariah customers in Tembelang District, Jombang Regency. Customer assistance is carried out 4 times a month. In the first week, the facilitator introduces and also assesses customers and assesses material recommendations. In the second week, the facilitator teaches the material to customers. In the third week, the facilitator reviews the material and practices. In the fourth week, the facilitator practices and closes. In the mentoring activity carried out on a customer named Mrs. Ida, she was recommended material in the form of a business-brand identity. Students made a banner design that was installed on her cart because the cart did not have Mrs. Ida's business name written on it but the name of a beverage product. The results of the material recommendations are very appropriate for the condition of her business because Mrs. Ida does not have a banner yet. It is hoped that by providing a business identity in the form of this brand, Mrs. Ida's business can be better known to the public.